Threat Intelligence and threat hunting (Addison-Wesley Professional, 2022)
7+ Hours of Video Instruction 7+ hours of video training exploring key threat intelligence and threat hunting concepts Overview: A cybersecurity professional needs to understand threats, threat actors, and have a clear understanding of where attackers are trying to take advantage of vulnerabilities. With more than 7 hours of video training, Threat Intelligence and Threat Hunting LiveLessons provides learners with a look at where the vulnerabilities in software, cloud, and other attack surfaces exist. Throughout the course, the learner will explore how to classify threats, work with the vulnerabilities, and use common assessment methodologies. The course will also dive into understanding threats against Internet of Things, real-time operating systems, and cloud-based environments. Threat Intelligence and Threat Hunting LiveLessons is taught by expert trainer, author, and cybersecurity expert Aamir Lakhani using hands-on demos, in-depth discussions, and lightboard explanations. The course will cover the best practices for cybersecurity in a way that is easy to access and implement in real world situations. Topics include: Importance of Threat Data and Intelligence Utilizing Threat Intelligence to Support Organization Security Vulnerability Management Activities Analyzing Output from Common Vulnerability Assessment Tools Threats Associated with the Cloud and Specialized Technology Implementing Controls to Mitigate Attacks and for Software Vulnerabilities Analyzing Logs and Impact Analysis About the Instructor Aamir Lakhani is a leading senior security strategist. He is responsible for providing IT security solutions to major enterprises and government organizations. Mr. Lakhani creates technical security strategies and leads security implementation projects for Fortune 500 companies. Industries of focus include healthcare providers, educational institutions, financial institutions, and government organizations. Aamir has designed offensive counter-defense measures for the Department of Defense and national intelligence agencies. He has also assisted organizations with safeguarding IT and physical environments from attacks perpetrated by underground cybercriminal groups. His areas of expertise include cyber defense, mobile application threats, malware management, Advanced Persistent Threat (APT) research, and investigations relating to the Internet's dark security movement. Skill Level: Beginner Learn How To: Apply key threat intelligence and threat hunting concepts Understand and classify hot attacks are taking advantage of vulnerabilities Use common vulnerability assessment methodologies Understand threats against Internet of Things, real-operating systems, and cloud-based environments Who Should Take This Course: Cybersecurity Professionals Anyone interested in learning cyber security fundamentals Course Requirements: There is no required prerequisite About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.